Social Intervention as Key to Prevent and Intervene in Violent Radicalization - Pérez Viejo, Jesús Manuel; López, Aída; Torres Kumbrián, Rubén Darío (Peter Lang, 2024)
[Resumen no disponible]
Keywords: social intervention; violent radicalization